Measurement of the components of the tensor analyzing power in the reaction [γd → ppπ −] at high proton momenta; Physics of Atomic Nuclei; Vol. 78, iss. 1 - Gauzshteyn (Gauzshtein) V. V. Vyacheslav Valerjevich; Zevakov S. A.; Loginov A. Yu. Aleksey Yurievich; Mishnev S. I.; Neufeld V. V.; Nikolenko D. M.; Rachek I. A.; Sidorov A. A.; Stibunov V. N. Victor Nikolaevich; Toporkov D. K.; Shestakov Yu. V. (2015, 2015)
Title screen